Program Pembiasaan Adab Berbasis Mata Pelajaran Pendidikan Agama Islam untuk Sekolah Menengah Pertama Fase D - Yudi Efendi; Wido Supraha; Nesia Andriana (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The phenomenon of declining manners among students, such as lack of respect for teachers, weak responsibility for knowledge, and fading manners in social interactions, is a serious challenge in the world of education. This condition shows a gap between the mastery of religious material and the practice of adab values in everyday life. Therefore, this study aims to develop an Islamic Religious Education (PAI) subject-based adab habituation programme for phase D Junior High Schools, as a solution to systematically integrate adab values in the learning process. This research uses a Research and Development (R&D) approach with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were PAI teachers and students in grades VII, VIII and IX in two of the Islamic-based junior high schools. Data collection techniques included observation, interviews, documentation, and questionnaires, which were then analysed qualitatively and quantitatively. The results showed that the results of the needs analysis of the adab habituation programme obtained a percentage of 90%. The adab habituation programme was designed with 10 programme systematics, namely rationale, vision and mission, description of needs, objectives, programme components, service areas, operational plan (action plan), theme/topic development, evaluation, reporting and follow-up and budget. The programme developed through integration in PAI subjects was considered valid through material expert validation with a score of 93.75%, linguist validation with a score of 91.66%, and practitioners with a score of 94%. Validation by experts and practitioners showed a high level of feasibility, while the results of limited implementation showed an increase in students' civilised behaviour in the context of worship, learning and social interaction. The programme succeeded in reviving the dimension of manners in education, which has received less attention in PAI learning practices. Thus, this programme is recommended to be widely implemented in order to strengthen learners' manners and spirituality through a holistic, integrative, and applicable habituation approach in PAI learning.